Do salinity variations along the East Greenland shelf show imprints of increasing meltwater runoff? - Schiller‐Weiss, Ilana; Martin, Torge; Karstensen, Johannes; Biastoch, Arne (Journal of Geophysical Research: Oceans, 2023)
Accelerated melting of the Greenland Ice Sheet is considered a tipping element in the freshwater balance of the subpolar North Atlantic (SPNA). The East Greenland Current (EGC) and Coastal Current (EGCC) are the major conduits for transporting Arctic-sourced and Greenland glacial freshwater. Understanding freshwater changes in the EGC system and drivers thereof is crucial for connecting tipping elements in the SPNA. Using the eddy-rich model VIKING20X (1/20°) and Copernicus GLORYS12 (1/12°), we find that from 1993 to 2019 freshwater remains close to the shelf with interannual extremes in freshwater content (FWC) attributable to the imprint of Greenland melt only in years 2010 and 2012. Runoff increased significantly from 1995 to 2005 and Arctic freshwater export after 2005. Overall, regional wind patterns, sea ice melt and increasingly glacial ice and snow meltwater runoff along with the Arctic-sourced Polar Water set interannual FWC variations in the EGC system. We emphasize that these freshwater sources have different seasonal timing. South of 65°N sea ice melts year round and retreats to north of 65°N, where melt in summer prevails. Greenland runoff peaks in June–August with only some locations of year round discharge. Alongshore winds intensify in fall and winter where reduced onshore Ekman transport allows for freshwater to spread laterally in the EGC. We show that sea ice melt, runoff and wind can cause interannual variations of comparable magnitude. All of which makes attributing ocean freshening events to Greenland meltwater inflow at current magnitudes a major challenge.